High-speed precision motion control - Yamaguchi, Takashi; Hirata, Mitsuo; Pang, Chee Khiang (Boca Raton, FL : CRC Press, 2012)
'Written for researchers and postgraduate students in Control Engineering, as well as professionals in the Hard Disk Drive industry, this book discusses high-precision and fast servo controls in Hard Disk Drives (HDDs). The editors present a number of control algorithms that enable fast seeking and high precision positioning, and propose problems from commercial products, making the book valuable to researchers in HDDs. Each chapter is self contained, and progresses from concept to technique, present application examples that can be used within automotive, aerospace, aeronautical, and manufacturing engineering. MATLAB/SIMULINK codes for benchmark problems are available for download, upon purchase'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Motion control devices; Electric controllers